Poly (N-vinyl Carbazole) – Polypyrrole/graphene oxide nanocomposite material on tapered fiber for Q-switched pulse generation - Ahmad, Harith; Faruki, Md Jahid; Jasim, Ali Abdulhadi; Ooi, Shok Ing; Thambiratnam, Kavintheran (Elsevier, 2018)
A passively Q-switched fiber laser using a Saturable Absorber (SA) fabricated from a new Poly (N-vinyl Carbazole) – Polypyrrole/Graphene Oxide (PNVC-PPy/GO) nanocomposite material deposited on a tapered fiber is proposed and demonstrated. The PNVC-PPy/GO composition is deposited along a 3 mm length of the 6.5 cm tapered fiber which has a tapered waist of 8 µm. Q-switched pulses are obtained with repetition rates of 25.15–42.7 kHz and pulse widths of 5.74–2.48 μs over a pump power range of 12.8–40.0 mW. A maximum average power of 0.19 mW and pulse energy of 4.43 nJ are also observed. The proposed Q-switched maintains advantages of a simple design and low fabrication cost while at the same time generating high quality Q-switched pulses.